Efeito de solvatação explícita nas propriedades eletrônicas de peptóides fluorescentes via metodologia QM/MM sequencial - Souza, Shamon Henrique Feitosa de (2023)
In this work, we investigated the photophysical properties of four recently synthesized peptoids employing Quantum Chemistry calculations. The environment in which the solute is inserted can directly influence its properties, as the interactions of the solute with other molecules directly affect the geometric and electronic structure of the entire system. Therefore, in this work we use explicit solvation methods, in which each solvent molecule is explicitly treated and the total contribution of solvent molecules is included in the system, thus providing a better approximation between theoretical and experimental values. We studied the effect of explicit solvent treatment on the electronic properties of fluorescent peptoids, solvated in five different solvents, through computer simulations using a hybrid methodology (QM/MM). Sequentially to the Monte Carlo calculations (ASEC via DICE program) ab initio quantum calculations were performed in which we used several exchange-correlation functionals in order to identify which is the most suitable for the studied peptoids and analogous systems. The results obtained via theoretical calculations were compared with the experimental results published by Wender et al. (2016). With that, we developed a computational protocol comparable to the experimental values.